Ubiquitin E3 Ligase Ring1b/Rnf2 of Polycomb Repressive Complex 1 Contributes to Stable Maintenance of Mouse Embryonic Stem Cells - van der Stoop, Petra; Boutsma, Erwin A.; Hulsman, Danielle; Noback, Sonja; Heimerikx, Mike; Kerkhoven, Ron M.; Voncken, J. Willem; Wessels, Lodewyk F. A.; van Lohuizen, Maarten (PloS one, 2008)
Polycomb repressive complex 1 (PRC1) core member Ring1b/Rnf2, with ubiquitin E3 ligase activity towards histone H2A at lysine 119, is essential for early embryogenesis. To obtain more insight into the role of Ring1b in early development, we studied its function in mouse embryonic stem (ES) cells. We investigated the effects of Ring1b ablation on transcriptional regulation using Ring1b conditional knockout ES cells and large-scale gene expression analysis. The absence of Ring1b results in aberrant expression of key developmental genes and deregulation of specific differentiation-related pathways, including TGFbeta signaling, cell cycle regulation and cellular communication. Moreover, ES cell markers, including Zfp42/Rex-1 and Sox2, are downregulated. Importantly, retained expression of ES cell regulators Oct4, Nanog and alkaline phosphatase indicates that Ring1b-deficient ES cells retain important ES cell specific characteristics. Comparative analysis of our expression profiling data with previously published global binding studies shows that the genes that are bound by Ring1b in ES cells have bivalent histone marks, i.e. both active H3K4me3 and repressive H3K27me3, or the active H3K4me3 histone mark alone and are associated with CpG-'rich' promoters. However, deletion of Ring1b results in deregulation, mainly derepression, of only a subset of these genes, suggesting that additional silencing mechanisms are involved in repression of the other Ring1b bound genes in ES cells. Ring1b is essential to stably maintain an undifferentiated state of mouse ES cells by repressing genes with important roles during differentiation and development. These genes are characterized by high CpG content promoters and bivalent histone marks or the active H3K4me3 histone mark alone.